PEMILIHAN LOKASI BASE TRANSCEIVER STATION JARINGAN WIRELESS PITA LEBAR PADA INTERNET SERVICE PROVIDER (Studi Kasus : PT. Sarana Insan Muda Selaras Cabang Yogyakarta) - Ari Subowo; Faisal RM; Agus Mansur (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Selection of the optimal location of a Base Transceiver Station (BTS) is a very important decision for Internet Service Provider (ISP), because it can increase the new market. In the process of development of BTS should consider some criteria to obtain the optimal location of the BTS as business criteria, technical criteria and support criteria. The location of this research was conducted at PT. SIMS Branch Yogyakarta. The process of analysis is combining GIS and AHP. GIS methods is used to process spatial data from alternatives location of BTS and AHP is used for the analysis of decision making. The use of this method is excellent in decision-making with many criteria. The both combination will complement each other's weaknesses. In the process of determining an alternate location, spatial data were analyzed using GIS methods to obtain the alternatives location can be used as a BTS sites, each alternative is ALT 1 at Moh. Yamin street, ALT 2 at Gatotkaca street, ALT 3 at Ringan Harjo street and ALT 4 at Diponegoro street, each of the sites are located in district of Bantul, Yogyakarta. Then to determine the most optimal alternative of BTS sites can use AHP method. The results of process data using AHP show business criteria weights is 0.688; technical criteria weights is 0.238 and support criteria weights is 0.074. While the order of the selected alternative is ALT 4 has the highest value with the weight of 0.358; ALT 2 weights is 0319; ALT 1 weights is 0.213 and ALT 3 weights is 0.110.